Prevotellaceae Modulates Colorectal Cancer Immune Microenvironment to Assist Anti-PD-L1 Immunotherapy - Xu, Song; Kong, Jianqiao; Dai, Yang; Li, Hengping (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Colorectal cancer (CRC) stands as the third most prevalent cancer on a global scale. In recent years, immunotherapy, such as anti-PD-L1 treatment, has demonstrated promising therapeutic outcomes in CRC. However, studies have suggested that intestinal microbiota may influence the efficacy of anti-PD-L1 immunotherapy. This study aimed to investigate the linkage between intestinal bacteria and anti-PD-L1 therapy. Materials and Methods: Bioinformatics analysis was employed to study the correlation between the intestinal microbiota of CRC patients and immune infiltration. The study delved into the relationship between Prevotellaceae and immune-related genes in CRC. Mouse experiments were conducted to validate the association between Prevotellaceae abundance and the efficacy of anti-PD-L1 tumor treatment. Prevotellaceae abundance in mouse feces was assayed by 16S sequencing. Flow cytometry was utilized to assay immune cell infiltration in patient tumor tissues, while western blot and quantitative polymerase chain reaction (qPCR) assays measured IFN-γ, IL-2, and PD-L1 levels in tumor tissues. Results: The high immune cell infiltration group demonstrated reduced tumor purity when compared with the group displaying low immune cell infiltration. Substantial variances were discerned in the Stromal Score, Immune Score, ESTIMATE Score, and Tumor Purity among the 3 distinct subtypes. The community evenness in the gut microbiota of CRC patients from cluster 2 and cluster 3 subtypes displayed significant differences. Members of the Prevotellaceae family were significantly enriched in the gut microbiota of cluster 3 subtype patients. In vivo experiments ascertained the supportive role of Prevotellaceae in anti-PD-L1 immunotherapy. Conclusion: The facilitating effect of Prevotellaceae on anti-PD-L1 treatment was demonstrated in CRC. The findings suggest that elevating Prevotellaceae abundance may offer a new direction for assisting in CRC immunotherapy and provide a foundation for devising more effective CRC immunotherapeutic strategies. Cite this article as: Xu S, Kong J, Dai Y, Li H. Prevotellaceae modulates colorectal cancer immune microenvironment to assist anti-PD-L1 immunotherapy. Turk J Gastroenterol. 2024;35(12):909-921.